2011
DOI: 10.1161/circgenetics.110.958157
|View full text |Cite
|
Sign up to set email alerts
|

A Novel KCNJ2 Nonsense Mutation, S369X, Impedes Trafficking and Causes a Limited Form of Andersen-Tawil Syndrome

Abstract: Background-Mutations in KCNJ2, a gene encoding the inward rectifier K ϩ channel Kir2.1, are associated with Andersen-Tawil syndrome (ATS), which is characterized by (1) ventricular tachyarrhythmias associated with QT (QU)-interval prolongation, (2) periodic paralysis, and (3) dysmorphic features. Methods and Results-We identified a novel KCNJ2 mutation, S369X, in a 13-year-old boy with prominent QU-interval prolongation and mild periodic paralysis. The mutation results in the truncation at the middle of the cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…32,33 More recently, we reported an S369X mutation located close to this ER export signal that impedes ER-Golgi transport. 7 We tested the trafficking function of four mutations, and only G144D mutation showed a trafficking defect ( Figure 5). Our results suggest that the phenotype expression variability of KCNJ2 mutations may be influenced by the topological location of mutations; however, the other possibilities, for example, environmental factors, modifier genes, or SNPs, 34 remain unstudied.…”
Section: Kimura Et Al Phenotype Variability In Kcnj2 Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 More recently, we reported an S369X mutation located close to this ER export signal that impedes ER-Golgi transport. 7 We tested the trafficking function of four mutations, and only G144D mutation showed a trafficking defect ( Figure 5). Our results suggest that the phenotype expression variability of KCNJ2 mutations may be influenced by the topological location of mutations; however, the other possibilities, for example, environmental factors, modifier genes, or SNPs, 34 remain unstudied.…”
Section: Kimura Et Al Phenotype Variability In Kcnj2 Mutationsmentioning
confidence: 99%
“…3 Since the first discovery of a mutation in this disease in 2001, 4 we have extensively examined KCNJ2 mutations in patients suspected of having ATS. [5][6][7] In 2007, we described both the clinical and genetic features of 23 patients (13 probands and 10 family members) and reported that the identification rate of KCNJ2 mutation in this cohort was 100% if the patients satisfied Ն2 features of ATS. 8 On a closer inspection, however, we noticed that Ϸ30% of the KCNJ2 mutation carriers lacked 2 of the ATS features: frequent PVC, bidirectional or polymorphic ventricular tachycardias (bVT or pVT), with QT or QU prolongation, without periodic paralysis or dysmorphic features.…”
mentioning
confidence: 99%
“…133 More recently, a naturally occurring KCNJ2 mutation in the C terminus (S369X), located immediately upstream of this endoplasmic reticulum export signal, was shown to cause a limited form of Andersen-Tawil syndrome (LQT7) by impeding transportation from the endoplasmic reticulum to Golgi (step 5 in Figure 3). 134 Most KCNH2 mutations have been reported to reduce hERG currents by a trafficking-deficient mechanism (step 6 in Figure 3). 131 Several trafficking-refractory KCNQ1mutations are also known, of which T587M in the C-terminal region was the first reported.…”
Section: Diverse Mechanisms Underlie the Generation Of Cardiac Potassmentioning
confidence: 99%
“…New mutations continue to be identified [25][26][27][28]. The recently described S369X mutation causes a loss of the endoplasmic reticulum export motif and impaired trafficking of the channel to the plasma membrane [28].…”
Section: Kcnj2 and Kcnj18 And Periodic Paralysismentioning
confidence: 99%